Open-space learning : a study in interdisciplinary pedagogy - Monk, Nicholas; Rutter, Carol Chillington; Neelands, Jonothan; Heron, Jonathan (The WISH List Ser., 2015)
A unique resource for educators wishing to develop a workshop model of teaching and learning. Despite the proliferation of virtual learning there is still real value to interaction in the classroom. The authors show how the techniques of the theatrical rehearsal room are applicable and effective across a wide range of disciplines.